Proved
Step-by-step explanation:
To prove x^m · x^n=x^m+n, let's assign numbers to x, m and n
let x = 2
m = 3, n = 4
x^m · x^n = 2^3 . 2^4
x^m+n = 2^(3+4)
Solve each of the above seperately and comparew the answer:
![\begin{gathered} x^m* x^n=2^3*2^4 \\ =\text{ (2}*2*2)*(2*2*2*2) \\ =\text{ 8}*16 \\ =\text{ }128 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mt5mrth2r3uk8lbbobwo5vbdl662gm94jj.png)
![\begin{gathered} x^(m+n)=2^(3+4) \\ =2^7\text{ = 2}*2*2*2*2*2*2 \\ =\text{ 128} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zjmma7ba40brivglr96kkn4020d8fh7r3l.png)
![\begin{gathered} sincex^m* x^n\text{ = 128} \\ \text{and x}^(m+n)\text{ = 128} \\ \text{Therefore, }x^m* x^n\text{ = x}^(m+n) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uja0fx03wu6np2vk7h516r8sv515hzhan5.png)
This expression x^m · x^n=x^m+n has been proved to be equal